Mainstreaming state auxiliary agency to handling revenge porn victims in Indonesia, 2020-2021 - Pamela Setya Miliasari; Dede Sri Kartini; Nandang Alamsah Delianoor (Department of Government Studies Universitas Muhammadiyah Makassar, 2023)
The state responded to the issue of violence against women by establishing an independent state agency, namely National Commission on Violence against Women. However, National Commission on Violence against Women faced numerous obstacles in its handling of cases, particularly regarding gender-based violence online, which had become the most discussed topic, and the largest case was revenge porn type in Indonesia. The purpose of this study was to analyze the authority of National Commission on Violence against Women in handling victims of revenge porn in Indonesia from 2020-2021. This study utilized theories of authority, state auxiliary organs, government administration, and revenge porn. The method used in this study was qualitative with a descriptive qualitative approach because the researcher wanted to describe the phenomenon found regarding National Commission on Violence against Women handling of the surge in revenge porn cases. Data collection techniques included observation, interviews, documentation, and a literature review conducted at National Commission on Violence against Women. The results of this study, viewed from the theory of authority, could be reviewed in terms of regulation, management, and supervision, it indicating that National Commission on Violence against Women had implemented its mandate in accordance with applicable Presidential Decrees. However, the process still faced many challenges, such as regulations, budget allocation, and access. National Commission on Violence against Women implemented various programs to address these challenges, including annual reports, publication and documentation, learning forums, monitoring, campaigns, and advocacy, and these programs were carried out by enhancing cooperation among government institutions, NGOs, and the public.